Perilaku Pencegahan Covid-19 pada Pendonor Darah di Palang Merah Indonesia Kota Malang - Mawarni, Dian; Fudhula'i, Ari Sihabul; Azzahra, Annisa Aulia; Asadullah, Autio Reza; Roidah, Hanin Dianti; Hapsari, Anindya (Universitas Negeri Malang, 2024)
Covid-19 is an important agenda for discussion. All countries around the world are implementing a lockdown. The number of Covid-19 reached 15,424 cases in Malang City. The aim of the study was to determine the prevention of Covid-19 in blood donors at the Indonesian Red Cross in Malang City as a preparedness effort. Qualitative method, obtained by distributing questionnaires in the blood transfusion unit of the Indonesian Red Cross in Malang City. The research design used observational analytic with a cross sectional approach. The research population is PMI Malang blood donors. The research sample consisted of 35 people taken based on inclusion and exclusion criteria using random sampling. The results: Compliance with mobility (54%), Using a mask (83%), Washing hands (66%), Use of Hand Sanitizer (51%), Social Distancing (54%), Consumption of healthy food (60%), Regular exercise (48%) ), Sunbathing in the morning (43%), Consumption of vitamins (43%) and Use of Disinfection (25%). Most of the respondents have implemented health protocols very well, there are new habits to improve health status. The spread of the Covid-19 virus can be prevented by implementing new clean and healthy living habits such as wearing masks, using hand sanitizers, washing hands, practicing social distancing, consuming healthy and nutritious food, exercising regularly, sunbathing in the morning and consuming additional vitamins. By properly implementing health protocols, both individuals and groups can improve health status and maintain health.